World Federation Of Occupational Therapists’ Position Statement On Telehealth (Int J Telerehabil, 2014)
The purpose of this document is to state the World Federation of Occupational Therapists’ (WFOT) position on the use of telehealth for the delivery of occupational therapy services. Telehealth is the use of information and communication technologies (ICT) to deliver health-related services when the provider and client are in different physical locations. Additional terms used to describe this service delivery model include: tele-occupational therapy, telerehabilitation, teletherapy, telecare, telemedicine, and telepractice, among other terms. Telehealth may be used by occupational therapy practitioners for evaluation, intervention, monitoring, supervision, and consultation (between remote therapist, client, and/or local health-care provider) as permitted by jurisdictional, institutional, and professional regulations and policies governing the practice of occupational therapy. Occupational therapy services via telehealth should be appropriate to the individuals, groups and cultures served, and contextualized to the occupations and interests of clients. Important considerations related to licensure/registration, collaboration with local occupational therapists, client selection, consent to treat, professional liability insurance, confidentiality, personal and cultural attributes, provider competence/standards of care, reimbursement/payer guidelines, and authentic occupational therapy practice are discussed.